2014
DOI: 10.1515/bmc-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

The MDM2 gene family

Abstract: MDM2 is an oncoprotein that blocks p53 tumor suppressor-mediated transcriptional transactivation, escorts p53 from the cell nucleus to the cytoplasm, and polyubiquitylates p53. Polyubiquitylated p53 is rapidly degraded in the cytoplasm by the 26S proteasome. MDM2 is abnormally upregulated in several types of cancers, especially those of mesenchymal origin. MDM4 is a homolog of MDM2 that also inhibits p53 by blocking p53-mediated transactivation. MDM4 is required for MDM2-mediated polyubiquitylation of p53 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 80 publications
0
65
1
Order By: Relevance
“…MDM2 is an oncoprotein that blocks p53 tumor suppressormediated transcriptional transactivation [10]. A deeper understanding of MDM2 regulation will help us to develop new and more effective strategies for ischemic stroke treatment that target MDM2 and activate p53 signaling in cells, owing to the critical role MDM2 plays in human disease.…”
Section: Introductionmentioning
confidence: 99%
“…MDM2 is an oncoprotein that blocks p53 tumor suppressormediated transcriptional transactivation [10]. A deeper understanding of MDM2 regulation will help us to develop new and more effective strategies for ischemic stroke treatment that target MDM2 and activate p53 signaling in cells, owing to the critical role MDM2 plays in human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent MDM2amp was the most common amplification identified in our series of METex14 cases, and it has been identified as an oncogenic event in diverse tumor types acting through negative regulation of p53 function through ubiquination. 27,28 CBL is the ubiquitin ligase implicated as being primarily responsible for ubiquitination of MET due to the presence of a tyrosine kinase binding domain. 29 While METex14 protein lacks a tyrosine kinase binding domain, it is unknown whether MDM2amp is a compensatory mechanism to increase ubiquitination of MET through a different portion of MET protein or an event independent of METex14 alterations.…”
mentioning
confidence: 99%
“…Rezaie et al reported MDM2 protein expression and limited polymorphisms in a small sample of canine tumors including mammary carcinoma and lymphoma,23 and we observed protein expression in melanomas by IHC. MDM2 is the central regulator of p53 by mediating its ubiquitination and nuclear and cytoplasmic degradation 24. Thus, by its action MDM2 suppresses p53 and overexpression of MDM2 is linked to an alternative pathway for wild‐type p53‐mediated oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 is the central regulator of p53 by mediating its ubiquitination and nuclear and cytoplasmic degradation. 24 Thus, by its action MDM2 suppresses p53 and overexpression of MDM2 is linked to an alternative pathway for wild-type p53-mediated oncogenesis. E2F1, a negative regulator of the tumor suppressor retinoblastoma gene, is linked to MDM2-p53 pathway in oncogenesis.…”
Section: Discussionmentioning
confidence: 99%